2017
DOI: 10.33736/bjrst.591.2017
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Synthesis of Pyrazine and Its Derivatives

Abstract: Pyrazine is a kind of natural product which can be found in plants, animals, insects, marine organisms andmicroorganisms. The main function of pyrazine in living organisms is used as flavor of the raw foods. Pyrazine and its derivatives were also produced in industries mainly for fragrance, flavor and pharmaceutical applications. This review describes the historical development of pyrazine including the discovery and synthesis, to the recent synthetic approach of pyrazinium. In general, six synthetic approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Also, the commercially available mixtures of 7 and 8 were chromatographically separated to show that each distinctly affected the behavioral response of fire ants in an electroantennogram study . Given the broad chemosensory application of EDMPs, several accounts highlight industrial syntheses and separation of these commodity compounds to address production bottlenecks. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the commercially available mixtures of 7 and 8 were chromatographically separated to show that each distinctly affected the behavioral response of fire ants in an electroantennogram study . Given the broad chemosensory application of EDMPs, several accounts highlight industrial syntheses and separation of these commodity compounds to address production bottlenecks. …”
Section: Introductionmentioning
confidence: 99%
“…Today, AlkPyrs are assembled synthetically by condensation between dicarbonyls and diamino compounds (Scheme A) or biosynthetically between self-condensation of an aminocarbonyl ( 19 ), followed by oxidation on the proposed biosynthetic pathway to 325-EDMP ( 8 ) in Serratia marcescens (Scheme B). , Recently, 325-EDMP ( 8 ) was discovered as an active component with potential for plant disease management against oomycete pathogens . Given this broad chemosensory and potential antimicrobial applications of AlkPyrs, several studies highlight the synthesis and separation of these commodity chemicals. For a while, natural EDMP isomers were thought to be available only as mixtures by extraction from resources, such as coffee beans, raw plants, vegetables, fish, poultry, and beef …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of old organic methodologies for synthesising pyrazine and its derivatives were reported more than two centuries ago. The self-condensation of α-ketoamines or the combination of α-diketones with vicinal diamines followed by dehydrogenation are among the oldest synthesis reactions to produce pyrazines that continue to be exploited [320].…”
Section: Pyrazines: Applications and Synthesismentioning
confidence: 99%
“…Moreover, Park et al concluded that the cyclization of propylene glycol and ethylenediamine to give 2-methylpyrazine using CuO-ZnO-SiO2 catalyst showed outstanding results (84% of 2-metylpyrazine yield at ≈99% conversion) attributed to the combined effect of the dehydrogenation properties of CuO-SiO2 and the cyclization properties of ZnO-SiO2 [326]. Other catalytic systems with limited data in reference patents are based on copper-chromium, copper-zinc-chromium, or zinc phosphates with manganese [320]. In the same line, R. Anand et al reported the reaction of ethylenediamine and propylene glycol over ZnO-modified FER [327] and ZnO-modified ZSM-5 [328] catalysts, achieving yields close to 65% when working with an excess of ethylenediamine at 450 ºC.…”
Section: Pyrazines: Applications and Synthesismentioning
confidence: 99%